Optimization of MBRs through integrated modelling: A state of the art - Giorgio Mannina; Marion Alliet; Christoph Brepols; Joaquim Comas; Marc Heran; Angel Robles; Ignasi Rodriguez-Roda; María Victoria Ruano; Valeria Sandoval Garcia; Ilse Smets; Jérôme Harmand (Journal of Environmental Management, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

WNT Signaling in Stem Cells: A Look into the Non-Canonical Pathway - Miguel Angel Sarabia-Sánchez; Martha Robles-Flores (Stem Cell Reviews and Reports, 2024)
Tissue homeostasis is crucial for multicellular organisms, wherein the loss of cells is compensated by generating new cells with the capacity for proliferation and differentiation. At the origin of these populations are the stem cells, which have the potential to give rise to cells with both capabilities, and persevere for a long time through the self-renewal and quiescence. Since the discovery of stem cells, an enormous effort has been focused on learning about their functions and the molecular regulation behind them. Wnt signaling is widely recognized as essential for normal and cancer stem cell. Moreover, β-catenin-dependent Wnt pathway, referred to as canonical, has gained attention, while β-catenin-independent Wnt pathways, known as non-canonical, have remained conspicuously less explored. However, recent evidence about non-canonical Wnt pathways in stem cells begins to lay the foundations of a conceivably vast field, and on which we aim to explain this in the present review. In this regard, we addressed the different aspects in which non-canonical Wnt pathways impact the properties of stem cells, both under normal conditions and also under disease, specifically in cancer. Graphical abstract

PM2.5-bound trace metals in an urban area of Northern Mexico during the COVID-19 pandemic: characterization, sources, and health risk - Stephanie Martínez Morales; Julia Griselda Cerón Bretón; Noel Carbajal; Rosa Maria Cerón Bretón; Reyna Lara Severino; Jonathan D.W. Kahl; Jair Rafael Carrillo Ávila; Simón Eduardo Carranco Lozada; Alberto Espinosa Guzmán; Ildefonso Esteban Pech Pech; Rocío Garcia Martinez; Juan Carlos Robles Heredia; et al. (Air Quality, Atmosphere & Health, 2023)

Biological processes modelling for MBR systems: A review of the state-of-the-art focusing on SMP and EPS - Giorgio Mannina; Bing-Jie Ni; Jacek Makinia; Jérôme Harmand; Marion Alliet; Christoph Brepols; M. Victoria Ruano; Angel Robles; Marc Heran; Hazal Gulhan; Ignasi Rodriguez-Roda; Joaquim Comas (Water Research, 2023)

TRANSDISCIPLINARY INNOVATION IN IRRIGATED SMALLHOLDER AGRICULTURE IN AFRICA - Jochen Froebrich; Eva Ludi; Sami Bouarfa; Dominique Rollin; Nebo Jovanovic; Maria Roble; Tarek Ajmi; Rami Albasha; Sékou Bah; Haithem Bahri; Gonzalo Barberá; Christy van Beek; et al. (Irrigation and Drainage, 2020)
Boosting the productivity of smallholder farming systems continues to be a major need in Africa. Challenges relating to how to improve irrigation are multi‐factor and multisectoral, and they involve a broad range of actors who must interact to reach decisions collectively. We provide a systematic reflection on findings from the research project EAU4Food, which adopted a transdisciplinary approach to irrigation for food security research in five case studies in Ethiopia, Mali, Mozambique, South Africa and Tunisia. The EAU4Food experiences emphasize that actual innovation at irrigated smallholder farm level remains limited without sufficient improvement of the enabling environment and taking note of the wider political economy environment. Most project partners felt at the end of the project that the transdisciplinary approach has indeed enriched the research process by providing different and multiple insights from actors outside the academic field. Local capacity to facilitate transdisciplinary research and engagement with practitioners was developed and could support the continuation and scaling up of the approach. Future projects may benefit from a longer time frame to allow for deeper exchange of lessons learned among different stakeholders and a dedicated effort to analyse possible improvements of the enabling environment from the beginning of the research process. © 2020 The Authors. Irrigation and Drainage published by John Wiley & Sons Ltd on behalf of International Commission for Irrigation and Drainage

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Instrumentation and control of anaerobic digestion processes: a review and some research challenges - Julie Jimenez; Eric Latrille; Jérôme Harmand; Angel Robles; José Ferrer; Daniel Gaida; Christian Wolf; Francis Mairet; Olivier Bernard; Victor Alcaraz-Gonzalez; Hugo Mendez-Acosta; Daniel Zitomer; et al. (Reviews in Environmental Science and Bio/Technology, 2015)

A novel ARH splice site mutation in a Mexican kindred with autosomal recessive hypercholesterolemia - Samuel Canizales-Quinteros; Carlos A. Aguilar-Salinas; Adriana Huertas-Vázquez; María L. Ordóñez-Sánchez; Maribel Rodríguez-Torres; José L. Venturas-Gallegos; Laura Riba; Salvador Ramírez-Jimenez; Rocío Salas-Montiel; Giovani Medina-Palacios; Ludivina Robles-Osorio; Angel Miliar-García; et al. (Human Genetics, 2005)

Induction of Somatic Embryogenesis and Plant Regeneration of ‘Ataulfo’ Mango (Mangifera indica) - Marisela Rivera-Domínguez; Miguel Angel Manzanilla-Ramírez; Manuel Robles-González; Miguel Angel Gómez-Lim (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Bottled-Water Quality in Metropolitan Mexico City - Esperanza Robles; Pedro Ramírez; Ma. Elena González; Ma. de Guadalupe Sáinz; Blanca Martínez; Angel Durán; Ma. Elena Martínez (Water, Air, & Soil Pollution, 1999)